2018
DOI: 10.1128/jcm.01700-17
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Accurate Identification of Candida auris by Using a Novel Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry (MALDI-TOF MS) Database (Library)

Abstract: T he newly emerging multidrug-resistant yeast Candida auris can cause serious infections and may be underrepresented, as it can be misidentified as other species (e.g., Candida haemulonii, Candida duobushaemulonii, or Saccharomyces cerevisiae) by some biochemical-based testing systems (1-4). Candida auris can be identified using research use only (RUO) libraries on matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) platforms, such as the Biotyper platform (Bruker, Billerica, MA), but may ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…In a study using the CDC panel of ten C. auris isolates, all ten C. auris isolates were identified correctly by the Vitek MS system after the direct extraction method, while 50% and 100% of C. auris isolates were correctly identified by the Biotyper after direct on-plate extraction and after full-tube extraction, respectively, indicating that the Biotyper performs better following the full-tube extraction method (8). Although direct on-plate FA extraction is simpler, Bruker Biotyper MS instructions recommend full-tube FA/ACN extraction for yeast identification (10,14). The reasons for the low rate of correct C. auris identification by Biotyper after direct on-plate extraction are poorly understood, but may be due to the characteristics of this pathogen, which renders solubilization of proteins difficult by simple extraction, or due to insufficient database entries to enable spectral matches because the C. auris database is designed for isolates after in-tube FA/ACN extraction.…”
Section: Discussionmentioning
confidence: 99%
“…In a study using the CDC panel of ten C. auris isolates, all ten C. auris isolates were identified correctly by the Vitek MS system after the direct extraction method, while 50% and 100% of C. auris isolates were correctly identified by the Biotyper after direct on-plate extraction and after full-tube extraction, respectively, indicating that the Biotyper performs better following the full-tube extraction method (8). Although direct on-plate FA extraction is simpler, Bruker Biotyper MS instructions recommend full-tube FA/ACN extraction for yeast identification (10,14). The reasons for the low rate of correct C. auris identification by Biotyper after direct on-plate extraction are poorly understood, but may be due to the characteristics of this pathogen, which renders solubilization of proteins difficult by simple extraction, or due to insufficient database entries to enable spectral matches because the C. auris database is designed for isolates after in-tube FA/ACN extraction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been detected on five continents within a few years of its first identification in 2009. Identification of C. auris requires specialised laboratory methodology such as matrix-assisted laser desorption/ionisation-time of flight (MALDI-TOF) mass spectrometry or sequencing of specific gene loci [2,3]. Reliance on traditional methods may lead to misidentification.…”
Section: Discussionmentioning
confidence: 99%
“…Species identification of C. auris can be challenging but is a prerequisite for adequate treatment and effective infection control measures [2,3,13]. Yet, seven EU/EEA countries still reported that a reference laboratory did not exist in their country.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome analysis suggests the emergence of five different C. auris clades [42,43]. It seems that by using reference databases containing more C. auris spectra from different clades, most isolates can be identified correctly with MALDI-TOF MS [44]. Thus, it is likely that with the currently updated Bruker MALDI Biotyper and bioMérieux Vitek MS reference libraries, that contain several C. auris spectra, excellent identification may be achieved.…”
Section: Discussionmentioning
confidence: 99%